Fretting and corrosion of metal liners from modular dual mobility constructs: a retrieval analysis. (1st July 2021) - Hemmerling, Kimberly J.; Weitzler, Lydia; Bauer, Thomas W.; Padgett, Douglas E.; Wright, Timothy M.
Abstract : Aims: Dual mobility implants in total hip arthroplasty are designed to increase the functional head size, thus decreasing the potential for dislocation. Modular dual mobility (MDM) implants incorporate a metal liner (e.g. cobalt-chromium alloy) in a metal shell (e.g. titanium alloy), raising concern for mechanically assisted crevice corrosion at the modular liner-shell connection. We sought to examine fretting and corrosion on MDM liners, to analyze the corrosion products, and to examine histologically the periprosthetic tissues. Methods: A total of 60 retrieved liners were subjectively scored for fretting and corrosion. The corrosion products from the three most severely corroded implants were removed from the implant surface, imaged using scanning electron microscopy, and analyzed using Fourier-transform infrared spectroscopy. Results: Fretting was present on 88% (53/60) of the retrieved liners, and corrosion was present on 97% (58/60). Fretting was most often found on the lip of the taper at the transition between the lip and the dome regions. Macrophages and particles reflecting an innate inflammatory reaction to corrosion debris were noted in six of the 48 cases for which periprosthetic tissues were examined, and all were associated with retrieved components that had high corrosion scores. Conclusion: Our results show that corrosion occurs at the interface between MDM liners and shells and that it can be associated with reactions in the local tissues, suggesting continued concern that this problem may become clinically important with longer-term use of these implants. Cite this article: Bone Joint J 2021;103-B(7):1238–1246.